V3 Recombinants Indicate a Central Role for CCR5 as a Coreceptor in Tissue Infection by Human Immunodeficiency Virus Type 1 - Chan, Stephen Y. (American Society for Microbiology, 1999)
Binding of the human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein gp120 to both CD4 and one of several chemokine receptors (coreceptors) permits entry of virus into target cells. Infection of tissues may establish latent viral reservoirs as well as cause direct pathologic effects that manifest as clinical disease such as HIV-associated dementia. We sought to identify the critical coreceptors recognized by HIV-1 tissue-derived strains as well as to correlate these coreceptor preferences with site of infection and dementia diagnosis. To reconstitute coreceptor use, we cloned HIV-1 envelope V3 sequences encoding the primary determinants of coreceptor specificity from 13 brain-derived and 6 colon-derived viruses into an isogenic (NL4-3) viral background. All V3 recombinants utilized the chemokine receptor CCR5 uniformly and efficiently as a coreceptor but not CXCR4, BOB/GPR15, or Bonzo/STRL33. Other receptors such as CCR3, CCR8, and US28 were inefficiently and variably used as coreceptors by various envelopes. CCR5 without CD4 present did not allow for detectable infection by any of the tested recombinants. In contrast to the pathogenic switch in coreceptor specificity frequently observed in comparisons of blood-derived viruses early after HIV-1 seroconversion and after onset of AIDS, the characteristics of these V3 recombinants suggest that CCR5 is a primary coreceptor for brain- and colon-derived viruses regardless of tissue source or diagnosis of dementia. Therefore, tissue infection may not depend significantly on viral envelope quasispeciation to broaden coreceptor range but rather selects for CCR5 use throughout disease progression.